2014
DOI: 10.1016/j.neuroimage.2013.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in the developing brain: A longitudinal study from 4 to 9months of age

Abstract: We characterize the development of intrinsic connectivity networks (ICNs) from 4 to 9 months of age with resting state magnetic resonance imaging performed on sleeping infants without sedative medication. Data is analyzed with independent component analysis (ICA). Using both low (30 components) and high (100 components) ICA model order decompositions, we find that the functional network connectivity (FNC) map is largely similar at both 4 and 9 months. However at 9 months the connectivity strength decreases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
71
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 63 publications
13
71
0
Order By: Relevance
“…Among these dynamic states, several similar states were found in the previous studies. For example, similar dynamic states as states 1, 3 and 5 were found in (Allen et al, 2013; Damaraju et al, 2014). …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Among these dynamic states, several similar states were found in the previous studies. For example, similar dynamic states as states 1, 3 and 5 were found in (Allen et al, 2013; Damaraju et al, 2014). …”
Section: Discussionsupporting
confidence: 74%
“…Several previous studies have shown that schizophrenia and bipolar patients can be discriminated at group-level by using the information on dysfunctional integration of the brain (Allen et al, 2012; Arbabshirani et al, 2013a; Damaraju et al, 2014; Friston, 2002b; Rashid et al, 2014). We hypothesized that disrupted functional integration in schizophrenia and bipolar patients as captured by FNC analysis reveal powerful information for automatic discriminative analysis at subject-level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neonates and very young infants, these individual compartments demonstrate locally correlated activity, but fail to synchronize into a coherent network (Damaraju et al, 2014; Fransson et al, 2007; Gao et al, 2009; Smyser et al, 2010; Wylie et al, 2014). Over the course of the first two years of life, these regions undergo a precise evolution to gradually bring the network ‘online’ (Damaraju et al, 2014; Gao et al, 2013; Gao et al, 2009). By two years of age, the network bears adult-like qualities, although coupling between distant anterior and posterior nodes of the network remain relatively low.…”
Section: Functional Brain Organization In Infants and Toddlersmentioning
confidence: 99%
“…Resting-state networks (RSNs) correspond to the brain's functional architecture during task-based fMRI studies [8][9][10][11]. Attributed to its intrinsic characteristic of minimum/no demands for subject participation, rsfMRI is recognized as an ideal tool for investigating the brain's functional maturation and neurodevelopment in infancy [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%